Comparison of TCSC and STATCOM for Damping Power System Oscillations - Tun, Thaw Tar; Swe, Pyone Lai (American Scientific Research Journal for Engineering, Technology, and Sciences, 2016)
Power system oscillation damping remains as one of the major concerns for secure and reliable operation of power systems. Power system oscillations occur due to the lack of damping torque at the generators’ rotors. The oscillation of the generators’ rotors causes the oscillation of other power system variables such as bus voltage. Flexible ac transmission systems (FACTS) devices with a suitable control strategy have the potential to increase the system stability margin. The damping problem is analyzed based on eigenvalue analysis and time-domain simulation. Case studies have been demonstrated on Myanmar National Grid using Power System Analysis Toolbox (PSAT). The oscillation damping by installing FACTS devices such as TCSC and STATCOM are studied in this paper and performance analysis of TCSC and STATCOM are compared in voltage supporting and power system oscillation damping.